Quality appraisal of clinical guidelines for Helicobacter pylori infection and systematic analysis of the level of evidence for recommendations - Ou, Jiayin; Li, Jiayu; Liu, Yang; Su, Xiaohong; Li, Wanchun; Zheng, Xiaojun; Zhang, Lang; Chen, Jing; Pan, Huafeng (PLOS ONE, 2024)
Objectives To systematically assess the quality of clinical practice guidelines (CPGs) for Helicobacter pylori (HP) infection and identify gaps that limit their development. Study design and setting CPGs for HP infection were systematically collected from PubMed, Embase, the Cochrane Library, the Cumulative Index to Nursing and Allied Health Literature, and six online guideline repositories. Three researchers independently used the AGREE Ⅱ tool to evaluate the methodological quality of the eligible CPGs. In addition, the reporting and recommendation qualities were appraised by using the RIGHT and AGREE-REX tools, respectively. The distribution of the level of evidence and strength of recommendation among evidence-based CPGs was determined. Results A total of 7,019 records were identified, and 24 CPGs met the eligibility criteria. Of the eligible CPGs, 19 were evidence-based and 5 were consensus-based. The mean overall rating score of AGREE II was 50.7% (SD = 17.2%). Among six domains, the highest mean score was for scope and purpose (74.4%, SD = 17.7%) and the lowest mean score was for applicability (24.3%, SD = 8.9). Only three of 24 CPGs were high-quality. The mean overall score of recommendation quality was 35.5% (SD = 12.2%), and the mean scores in each domain of AGREE-REX and RIGHT were all ≤ 60%, with values and preferences scoring the lowest (16.6%, SD = 11.9%). A total of 505 recommendations were identified. Strong recommendations accounted for 64.1%, and only 34.3% of strong recommendations were based on high-quality evidence. Conclusion The overall quality of CPGs for HP infection is poor, and CPG developers tend to neglect some domains, resulting in a wide variability in the quality of the CPGs. Additionally, CPGs for HP infection lack sufficient high-quality evidence, and the grading of recommendation strength should be based on the quality of evidence. The CPGs for HP infection have much room for improvement and further researches are required to minimize the evidence gap.